Nonlinear conduction via solitons in a topological mechanical insulator - Chen, Bryan Gin-ge; Upadhyaya, Nitin; Vitelli, Vincenzo (Proceedings of the National Academy of Sciences - PNAS, 2014)
Significance Mechanisms are zero-energy motions that are key to the operation of mechanical devices, from windshield wipers to robotic arms. We built and studied chain-like mechanisms of coupled rigid rotors that are topologically protected, which means that they are not affected by smooth changes in material parameters like their quantum analogues. These prototypes are examples of mechanical structures that we dub topological metamaterials. Their mechanical excitations are nonlinear solitary waves which are topologically protected and yet tunable by changing the geometry of the unit cell. Although the left and right edges of the sample are equivalent in terms of local constraint counting, the solitary waves can start propagating only from the edge singled out by the topological polarization of the chain.